Solve using elimination. x-2y=10
3x+y=-12
1 answer:
Answer:
x-2y=10-------equation 1
3x+y=-12-------equation 2
multiply equation 1 by 3 and subtract eqn 2 by equation 1 then we get,
3x-6y=30
3x+y=-12
(-) (-) (+)
---------------
-7y=42
or, -y= 42÷7
or, y=-6
put the value of y in equation 1
x-2×(-6)=10
or, x+12=10
or x=10-12
or, x = -2
therefore x = -2 and y=-6 ans.
You might be interested in
3/5 -3/10=
6/10 -3/10 =
3/10
It should be trimmed by 3/10 cm
That's a pretty confusing one. I think it's 10 minutes.
Answer:
26.6
Step-by-step explanation
3=10*k
3/10=.3
y=8
8=.3*x
8/.3=26.6